Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{4x +2}{15x^3y}\) + \(\dfrac{5y-3}{9x^2y}\) + \(\dfrac{x +1}{5xy^3}\)
=\(\dfrac{\left(4x+2\right)\cdot3y^2}{45x^3y^3}\) + \(\dfrac{\left(5y-3\right)\cdot5xy^2}{45x^3y^3}\) + \(\dfrac{\left(x+1\right)\cdot9x^2}{45x^3y^3}\)
=\(\dfrac{12xy^2+6y^2+25xy^3-15xy^2+9x^3+9x^2}{45x^3y^3}\)
=\(\dfrac{9x^3+9x^2+25xy^3-3xy^2+6y^2}{45x^3y^3}\)
Đáp án:
a.3x³−5x²+7xa.3x³−5x²+7x
b.−4x²y−10x²y+2xyb.−4x²y−10x²y+2xy
c.−x³+2x²+29x+20c.−x³+2x²+29x+20
d.2x⁴−3x³+2x²+3x−4d.2x⁴−3x³+2x²+3x−4
e.x²−4y²e.x²−4y²
h.2x²−6x+13h.2x²−6x+13
g.3xy⁴−12y²+2x²yg.3xy⁴−12y²+2x²y
f.−2x²y³+y−3f.−2x²y³+y−3
Giải thích các bước giải:
a.3x.(x²−5x+7)a.3x.(x²−5x+7)
=3x³−5x²+7x=3x³−5x²+7x
b.−2xy.(2x³+5x−1)b.−2xy.(2x³+5x−1)
=−4x⁴y−10xy²+2xy=−4x⁴y−10xy²+2xy
c.(x+4).(−x²+6x+5)c.(x+4).(−x²+6x+5)
=−x³+6x²+5x−4x²+24x+20=−x³+6x²+5x−4x²+24x+20
=−x³+2x²+29x+20=−x³+2x²+29x+20
d.(x²−1).(2x²−3x+4)d.(x²−1).(2x²−3x+4)
=2x⁴−3x³+4x²−2x²+3x−4=2x⁴−3x³+4x²−2x²+3x−4
=2x⁴−3x³+2x2+3x−4=2x⁴−3x³+2x2+3x−4
e.(x+2y).(x−2y)e.(x+2y).(x−2y)
=x²−(2y)²=x²−(2y)²
=x²−4y²=x²−4y²
h.(3x−1)²−7(x²+2)h.(3x−1)²−7(x²+2)
=9x²−6x+1−7x²−14=9x²−6x+1−7x²−14
=2x²−6x+13=2x²−6x+13
g.(6x²g.(6x²y⁵−xy³+4x³y²):2xy−xy³+4x³y²):2xy
=3xy⁴−12y²+2x²y=3xy⁴−12y²+2x²y
f.(−12x³y⁴+6xy²−18xy):6xyf.(−12x³y⁴+6xy²−18xy):6xy
=−2x³y³+y−3
a.x2-7x+10
⇔x2-2x-5x+10
⇔x(x-2)-5(x-2)
⇔(x-2)(x-5)
b.\(\left(12x^6y^4+9x^5y^3-15x^2y^3\right):3x^2y^3\)
=\(4x^4y+3x^3-5\)
=
x2-7x+10
= x2-5x-2x+10
=x(x-5)-2(x-5)
=(x-5)(x-2)
(12x6y4+9x5y3-15x2y3): 3x2y3
=4x4y+3x3-3
a) \(6xy+2y^3-15x-5y^2\)
\(=\left(2y^3-5y^2\right)+\left(6xy-15x\right)\)
\(=y^2\left(2y-5\right)+3x\left(2y-5\right)\)
\(=\left(y^2+3x\right)\left(2y-5\right)\)
a: =-1/5x^5y^2
b: =-9/7xy^3
c: =7/12xy^2z
d: =2x^4
e: =3/4x^5y
f: =11x^2y^5+x^6
a,3x3y3-15x2y2=3x2y2(xy-5)
b,2x(x-5y)+8y(5y-x)=2x(x-5y)-8y(x-5y)=(x-5y).(2x-8y)
c,(3x-1)2-16=(3x-1)2-42=(3x-1+4)(3x-1-4)=(3x+3)(3x-5)
d,x3-3x2+3x-1=x3-1-(3x2+3x)=x3-1-3x(x+1)=(x3-1-3x)(x+1)
e,125x3+1=(5x)3+13=(5x+1)(25x2-5x.1+12)
f,x3+6x2y+12xy2+8y3=x3+3.x2.2y+3.x.(2y)2+(2y)3=(x+2y)3
a) 3x(x + 1) - 5y(x + 1)
= (x + 1)(3x - 5y)
b) 3x(x - 6) - 2(x - 6)
= (x - 6)(3x - 2)
c) 4y(x - 1) - (1 - x)
= 4y(x - 1) + (x - 1)
= (x - 1)(4y + 1)
d) (x - 3)³ + 3 - x
= (x - 3)³ - (x - 3)
= (x - 3)[(x - 3)² - 1]
= (x - 3)(x - 3 - 1)(x - 3 + 1)
= (x - 3)(x - 4)(x - 2)
e) 7x(x - y) - (y - x)
= 7x(x - y) + (x - y)
= (x - y)(7x + 1)
h) 3x³(2y - 3z) - 15x(2y - 3z)²
= (2y - 3z)[3x³ - 15x(2y - 3x)]
= 3x(2y - 3x)[x² - 5(2y - 3x)]
= 3x(2y - 3x)(x² - 10y + 3x)
= 3x(2y - 3x)(x² + 3x - 10y)
k) 3x(x + 2) + 5(-x - 2)
= 3x(x + 2) - 5(x + 2)
= (x + 2)(3x - 5)
l) 18x²(3 + x) + 3(x + 3)
= (x + 3)(18x² + 3)
= 3(x + 3)(6x² + 1)
m) 7x(x - y) - (y - x)
= 7x(x - y) + (x - y)
= (x - y)(7x + 1)
n) 10x(x - y) - 8y(y - x)
= 10x(x - y) + 8y(x - y)
= (x - y)(10x + 8y)
= 2(x - y)(5x + 4y)
Bài 2:
a: \(=x^{n+19-14}=x^{n+5}\)
b: \(=x^{94-17-65}=x^{12}\)
15x^5y^3:x^2y^2=15x^3y